1991
DOI: 10.1093/oxfordjournals.aob.a088262
|View full text |Cite
|
Sign up to set email alerts
|

Density Effects on the Size Structure of Annual Plant Populations: An Indication of Neighbourhood Competition

Abstract: Size variability among plants has been observed to increase with higher stand density, leading to the speculation that resource distribution among competing plants is primarily asymmetric rather than symmetric. The relationships between size variability, stand density, and type of resource distribution among competing plants were investigated using a spatially explicit, individual-plant model of annual plant population dynamics. When plants varied in neighbourhood competition, size variability increased with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 19 publications
(36 reference statements)
2
48
1
3
Order By: Relevance
“…Some studies have concluded that a major factor generating size variation in crowded plant populations is the "size asymmetry" of competition: larger plants have a disproportionate advantage (for their relative size) in competition with smaller plants, suppressing their growth (Begon 1984;Weiner 1990;Schwinning and Weiner 1998). In simple models, increases in size inequality with density are observed only when competition is size asymmetric (Weiner and Thomas 1986), so the commonly observed increase in size inequality in populations grown at higher densities has been considered evidence in support of the hypothesis of size-asymmetric competition (Weiner 1990).Other researchers have argued that the importance of size-asymmetric competition has been exaggerated, and its existence has even been questioned (Turner and Rabinowitz 1983;Bonan 1991). Other phenomena, such as variation in exponential growth rates and variation in local crowding, might explain the patterns of size variation that have been attributed to size-asymmetric competition, such as the higher size inequality observed at higher densities.…”
mentioning
confidence: 99%
“…Some studies have concluded that a major factor generating size variation in crowded plant populations is the "size asymmetry" of competition: larger plants have a disproportionate advantage (for their relative size) in competition with smaller plants, suppressing their growth (Begon 1984;Weiner 1990;Schwinning and Weiner 1998). In simple models, increases in size inequality with density are observed only when competition is size asymmetric (Weiner and Thomas 1986), so the commonly observed increase in size inequality in populations grown at higher densities has been considered evidence in support of the hypothesis of size-asymmetric competition (Weiner 1990).Other researchers have argued that the importance of size-asymmetric competition has been exaggerated, and its existence has even been questioned (Turner and Rabinowitz 1983;Bonan 1991). Other phenomena, such as variation in exponential growth rates and variation in local crowding, might explain the patterns of size variation that have been attributed to size-asymmetric competition, such as the higher size inequality observed at higher densities.…”
mentioning
confidence: 99%
“…Além disso, estas mesmas plantas apresentaram maior estatura. Conforme Bonan (1991), as flutuações em tamanho de plantas caracterizam as condições em que se desenvolveram, sendo as maiores estaturas relacionadas com maiores densidades de semeaduras, que proporciona maior competição entre indivíduos. Assim, no cultivo a campo as plantas de trigo foram submetidas a maiores níveis A B Figura 1.…”
Section: Resultsunclassified
“…Assim, no cultivo a campo as plantas de trigo foram submetidas a maiores níveis A B Figura 1. Diagrama de correlações entre a ordem de emergência das plantas, diâmetro do pseudocolmo, comprimento da bainha foliar (estatura) e a escala de desenvolvimento foliar, determinada conforme Haun (1973), no colmo principal (Haun CP) e nos afilhos do coleóptilo (Haun A0), da primeira folha (Haun A1), da segunda folha (Haun A2) e da terceira folha (Haun A3), que em conjunto formam o somatório foliar por planta (Haun soma (Benjamin & Hardwick 1986, Bonan 1991. Assim, para se ter uma comparação válida entre os ambientes (campo e canteiros) seria necessário uma maior área de amostragem no cultivo a campo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Studies of competitive symmetry have shown that larger size may confer a disproportionate advantage for resource preemption (reviews in Weiner, 1990;Casper and Jackson, 1997;Schwinning and Weiner, 1998) which can affect the size distribution of individuals in crowded populations (e.g. Weiner, 1985;Weiner et al, 2001; but see Bonan, 1991). The benefits of larger size are also evident in studies of competitive ability (e.g.…”
Section: Introductionmentioning
confidence: 99%